How to teach evidence-based medicine to urologists - Hajebrahimi, Sakineh (Medknow Publications & Media Pvt Ltd, 2011)
The goal of this article is to help develop, disseminate, and evaluate resources that can be used to practice and teach EBM for urology residents and continuing education of urologists to reduce the gap between research and clinical practice. Urology departments should build capacity for residents to shape the future of quality and safety in healthcare through translating evidence into practice. Cutting edge approaches require knowing how to teach Evidence-based urology, to make Bio-statistics easy to understanding and how to lead improvement at every level. The authors shared their experience about ‘what works’ in a surgical department to building an Evidence-based environment and high quality of cares.